Efektivitas Pembinaan Kesadaran Berbangsa Dan Bernegara Terhadap Narapidana Dalam Menyadari Kesalahannya: (The Effectiveness of National and State Awareness Building Against Prisoners in Realizing Their Errors) - Aditya Rafif Widyardi; Padmono Wibowo (JOURNAL SAINS STUDENT RESEARCH, 2023)
become a better society is very important, material and spiritual guidance must be carried out in a balanced manner, because this is a major thing in supporting prisoners easily in living their lives after completing their criminal period. The criminal treatment is considered to have a deterrent effect on perpetrators of criminal acts. However, in reality, providing a deterrent effect is not effective, this is evident from the many repetitions of criminal acts (recidive) in the community. This study discusses the implementation of the development of prisoners in the Correctional Institution and the effectiveness of the implementation of national and state awareness development for prisoners in the Class IIA Salemba Prison. Based on the articles in PP No. 31 of 1999 concerning the Guidance and Guidance of Correctional Inmates, the stages of coaching for prisoners are Early Stage Development, Advanced Stage Development, and Final Stage Coaching. In the Class IIA Salemba Prison, the factors that support the successful implementation of the process of Correctional Inmates at the Class IIA Salemba Prison are the condition of the employees and the condition of the occupants. Guidance at the Class IIA Salemba Prison is not effective due to overcapacity and limited facilities and infrastructure.